(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: In this study, we utilize the IBM-1 model to theoretically investigate the structural characteristics of , with a specific emphasis on a nucleus consisting of 5 bosons. Employing the IBM-1, an innovative interacting boson model, we analyze the nuclear structure. Materials and Methods: In our theoretical exploration, we delved into the nuclear architecture of Molybdenum. Employing the Interacting Boson Model (IBM-1), we identified the pertinent Hamiltonian to scrutinize the isotope in this research endeavor. Results: Our investigation delved into the symmetry limit of the proposed nucleus, unveiling its stable nature within the SU(5) dynamical symmetry domain. To optimize alignment with observed energy states in experiments, we meticulously determined the parameters in the IBM-1 Hamiltonian equation. Furthermore, our research extends to the computation of B(E2) transitions, quadrupole moments, and energy levels across all bands for the examined nucleus. Conclusions: Our investigation reveals the stability of the nucleus in the isotope, showcasing the presence of SU(5) dynamical symmetry. These findings offer fresh perspectives by suggesting additional electric quadrupole moments.